Carbadox has both temporary and lasting effects on the swine gut microbiota - Looft, Torey; Allen, Heather K.; Casey, Thomas A.; Alt, David P.; Stanton, Thaddeus B. (Frontiers in Microbiology, 2014)
Antibiotics are used in livestock and poultry production to treat and prevent disease as well as to promote animal growth. Carbadox is an in-feed antibiotic that is widely used in swine production to prevent dysentery and to improve feed efficiency. The goal of this study was to characterize the effects of carbadox and its withdrawal on the swine gut microbiota. Six pigs (initially 3-weeks old) received feed containing carbadox and six received unamended feed. After 3-weeks of continuous carbadox administration, all pigs were switched to a maintenance diet without carbadox. DNA was extracted from feces (n=142) taken before, during, and following (6-week withdrawal) carbadox treatment. Phylotype analysis using 16S rRNA sequences showed the gradual development of the non-medicated swine gut microbiota over the 8-week study, and that the carbadox-treated pigs had significant differences in bacterial membership relative to non-medicated pigs. Enumeration of fecal Escherichia coli showed that a diet change concurrent with carbadox withdrawal was associated with an increase in the E. coli in the non-medicated pigs, suggesting that carbadox pretreatment prevented an increase of E. coli populations. In-feed carbadox caused striking effects within four days of administration, with significant alterations in both community structure and bacterial membership, notably a large relative increase in Prevotella populations in medicated pigs. Digital PCR was used to show that the absolute abundance of Prevotella was unchanged between the medicated and non-medicated pigs despite the relative increase shown in the phylotype analysis. Carbadox therefore caused a decrease in the abundance of other gut bacteria but did not affect the absolute abundance of Prevotella. The pending regulation on antibiotics used in animal production underscores the importance of understanding how they modulate the microbiota and impact animal health, which will inform the search for antibiotic alternatives.